Quality of Life Following Salvage Endoscopic Nasopharyngectomy in Patients With Recurrent Nasopharyngeal Carcinoma: A Prospective Study - Li, Wanpeng; Lu, Hanyu; Liu, Juan; Liu, Quan; Wang, Huan; Zhang, Huankang; Sun, Xicai; Hu, Li; Zhao, Weidong; Gu, Yurong; Li, Houyong; Wang, Dehui (Frontiers in Oncology, 2020)
Background: This study aimed to assess the effect of endoscopic nasopharyngectomy in patients with recurrent nasopharyngeal carcinoma (NPC) on site-specific and sinonasal-related quality of life (QoL) before and after surgery using validated instruments. Methods: Consecutive adult patients with recurrent NPC, who were treated via salvage endoscopic nasopharyngectomy, were prospectively enrolled at a single institution from January 2018 to December 2019. Each patient completed the Anterior Skull Base Questionnaire (ASBQ) and the 22-Item Sino-Nasal Outcome Test (SNOT-22) preoperatively, and then at regular intervals after surgery to assess their perceived QoL. Results: Forty patients fulfilled the inclusion criteria. The median follow-up was 12 months (range, 2–24 months). Overall scores on the ASBQ and SNOT-22 at 3 or 12 weeks after surgery decreased significantly compared with before surgery (p < 0.05). At 6 months and 1 year postoperatively, there was no significant difference from the preoperative score. Subtotal resection was associated with worse overall ASBQ scores at 6 months and 1 year after endoscopic nasopharyngectomy (p < 0.05). Worse QoL was also associated with advanced T stage (rT3 and rT4) and pathological World Health Organization type III. Sex, age (<50 years), tumor necrosis, lymph node metastasis, and use of a nasoseptal flap approach did not impact postoperative QoL. Conclusions: Site-specific and sinonasal-related QoL, measured using validated tools, demonstrated an overall maintenance of postoperative compared with preoperative QoL. Endoscopic endonasal resection is a valuable management choice in patients with recurrent NPC. In addition, subtotal resection was an important factor that negatively influenced postoperative QoL; as such, gross-total resection should be attempted in all patients to optimize QoL after surgery.